Cover Picture: Self‐Heating Approach to the Fast Production of Uniform Metal Nanostructures (ChemNanoMat 1/2016). Issue 1 (18th December 2015) - Yin, Xi; Wu, Jianbo; Li, Panpan; Shi, Miao; Yang, Hong
Abstract : Heat released from exothermic reaction between a popular pair of capping ligands, long‐carbon chain amine and carboxylic acid, was used as the main energy source for the preparation of a variety of metal nanocrystals, which are illustrated on the Front Cover. Uniform gold nanowires and nanoparticles, and concave tetrahedral Pd nanoparticles were synthesized using this self‐heating method. This synthetic route arises from the unique heating method from ligand‐based chemical reactions. Background: NGC 6302 Nebula, from NASA, ESA and the Hubble SM4 ERO Team. More information can be found in the Communication by H. Yang, et al. onpage 37 in Issue 1, 2016 (DOI:10.1002/cnma.201500123 ).